Ս. Հովհաննես Օձնեցու կերպարը հայ ձեռագրական արվեստում - Սեդա Մանուկյան; Գառնիկ Հարությունյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Образ Ованеса Одзнеци очень интересно изображался в армянском искусстве, в частности в миниатюре. В этих миниатюрах Одзнеци не только в образе духовного лидера, но и святого. Он также представлен в разделах легенд, связанных с его именем, что становится одним из особенностей его иконографии. The image of Hovhannes Odznetsi had many interesting manifestations in the Armenian art, particularly in the Armenian miniature.In these miniatures, Hovhannes Odznetsi, besides having an image of a spiritual leader, is presented as a saint. He is also portrayed according to the episodes of the legends associated with his name, which has become one of the pictorial peculiarities of Odznetsi’s iconography.
Keywords: Biography; Auxiliary Sciences of History; Fine Arts; Illuminating of Manuscripts and Books